2021
DOI: 10.3390/ijerph18115762
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and COVID-19 Pandemic Perception in Malaysia: A Cross-Sectional Study

Abstract: Pregnant women are susceptible to COVID-19 complications due to gestation-related physiological changes. We aimed to evaluate the level of maternal knowledge, perception, and practice during the pandemic. A cross-sectional study was conducted during the Malaysian Movement Control Order (MCO) between April and June 2020. A self-administered electronic questionnaire that included the knowledge and practice domains was distributed. A newly designed set of questions was used to evaluate (1) women’s perception of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 34 publications
(46 reference statements)
2
19
0
1
Order By: Relevance
“…Women's cultural background, which is influenced by race and religion; often plays a role in maternal perception, practice, and attitude toward the COVID-19 pandemic. Our previous published findings demonstrated that Malay women demonstrated a more positive attitude toward the MCO ( 22 ). A study from our neighboring country Singapore showed that pregnant Malay women were more likely to practice safe distancing and frequent hand sanitizing compared to the Chinese ( 47 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Women's cultural background, which is influenced by race and religion; often plays a role in maternal perception, practice, and attitude toward the COVID-19 pandemic. Our previous published findings demonstrated that Malay women demonstrated a more positive attitude toward the MCO ( 22 ). A study from our neighboring country Singapore showed that pregnant Malay women were more likely to practice safe distancing and frequent hand sanitizing compared to the Chinese ( 47 ).…”
Section: Discussionmentioning
confidence: 97%
“…Socio-demographics and clinical data were included in the data collection. We also evaluated the maternal knowledge, perception, and practice during the COVID-19 pandemic as part of this research and the relevant results had already been published ( 22 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, similar difficulties in prenatal care happen in Malaysia [27]. It has been reported that 22.4% of pregnant women perceived that their antenatal appointments were affected, 34.7% felt anxious when their spouse was not allowed to accompany during antenatal visit, 20.7% were worried about having to give birth during the lockdown, 23.6% received unclear advice on where to deliver, and 19.8% felt worried that their spouse cannot accompany them during childbirth [27].…”
Section: Introductionmentioning
confidence: 95%
“…Ilska et al (2021) highlighted that the pandemic disrupted obstetric appointments such as the regularity of appointments, availability of medical care in obstetric-related emergent situations, and involvement in antenatal classes [26]. Likewise, similar difficulties in prenatal care happen in Malaysia [27]. It has been reported that 22.4% of pregnant women perceived that their antenatal appointments were affected, 34.7% felt anxious when their spouse was not allowed to accompany during antenatal visit, 20.7% were worried about having to give birth during the lockdown, 23.6% received unclear advice on where to deliver, and 19.8% felt worried that their spouse cannot accompany them during childbirth [27].…”
Section: Introductionmentioning
confidence: 99%